The Treaty on the Prohibition of Nuclear Weapons: Is There a Better Alternative? - M. N. Lysenko; A. D. Ostapova (Московский журнал международного права, 2022)
INTRODUCTION. Te Treaty on the Prohibition of Nuclear Weapons (TPNW) which came into force in January 2021 divided the international society into two groups: its ardent supporters and opponents. Te vast majority of the parties to the Treaty are the states which have neither nuclear potential, nor political inﬂuence in the international nuclear agenda. In contrast, all the nuclear-weapon powers and almost all states with nuclear infrastructures refused to participate in the TPNW. Te Treaty contains an array of legal ﬂaws, does not require any verifcation mechanism or even time-frame for nuclear weapons destruction.MATERIALS AND METHODS. Te study is based on the international treaties in the sphere of nuclear non-proliferation and disarmament, resolutions of international organizations, ofcial statements, and joint documents of the heads of states and of the fve nuclear-weapon states (P5). Materials used for the analysis include scholar works of Russian and foreign researches in the international security law and nuclear law. Te research is based on general methods of study such as systematic approach, induction and deduction, logical forecasting, and specifc methods including historical and legal comparative methods.RESEARCH RESULTS. Te article starts with the history of international eﬀorts of nuclear weapons prohibition and approaches of leading powers. Specifc legal drawbacks inherent in the TPNW were exposed which proves that the Treaty is in fact a legally inconsistent document. At the same time antinuclear attitudes behind the Treaty should be understood and taken into consideration. Tere is a strong need for a constructive alternative to the TPNW.DISCUSSION AND CONCLUSIONS. By comparing the various states’ approaches and legal opinions, the authors come up with a “Road Map” of actions which could become a real counterweight to the hasty and ill-considered decisions to prohibit nuclear weapons. Among those actions is the movement along two parallel tracks. Te frst one is Russian-American talks on further nuclear arms reductions which should include all strategic factors. Te second one is a gradual involvement in the process of other nuclearweapon powers through informal mechanism of consultations of the P5. Te article prescribes how to fll this mechanism with measures of transparency, confdence building and predictability.